Identifying Entrepreneurial Marketing Indicators in the Import and Export of Grains and Animal Feed Using a Grounded Theory Approach - Zargaran, Kaveh; Vazifehdoust, Hosein; Rahnamae Roodposhti, Fereydoun (Management Strategies and Engineering Sciences, 2026)
This study was conducted with the aim of identifying entrepreneurial marketing indicators in the import and export of grains and animal feed using a grounded theory approach. The present research is grounded in an empiricist philosophy and was carried out using a deductive–inductive approach. In terms of purpose, it is a basic research study conducted through a qualitative methodology. Data collection instruments included interviews and questionnaires. To analyze the expert interviews, the grounded theory method was employed. In addition, the identified indicators were validated using the fuzzy Delphi method. Finally, the final research model was developed. Data analysis was conducted using MaxQDA software. The statistical population of this study consisted of academics and managers with extensive executive experience in the fields of entrepreneurship and export, as well as managers of companies operating in the import and export of grains and animal feed. Sampling was conducted using a non-probability, purposive method. The identified indicators were categorized into 17 main dimensions, including farmers’ participation in entrepreneurial marketing, organizational knowledge and innovation, organizational structure, global competitiveness, logistics management, entrepreneurial personality traits, product characteristics, communication improvement, strategy formulation, logistics costs, existing barriers, marketing strategy, government presence as a facilitator, utilized infrastructure, development of an entrepreneurial marketing network, and facilitation of international communications. The results indicate that the formation and development of entrepreneurial marketing require governmental actions and support alongside systematic and coordinated planning. Moreover, the establishment of an effective and dynamic entrepreneurial environment, in turn, provides the foundation for empowering farmers, exporters, importers of grains and animal feed, and stakeholders in the agricultural sector.